A study of psychiatric co-morbidity among alcohol dependents - Kanwar, Pankaj; Sharma, Ravi C.; Sharma, Dinesh D.; Kanwar, Neeraj (International Journal of Research in Medical Sciences, 2017)
Background: The alcohol use disorders are frequently associated with other co-morbid psychiatric disorders. The aim of this study was to describe the demographic variables, drinking history and psychiatric co-morbidity in alcohol dependent subjects. Methods: In this study, 40 consecutive patients were enrolled. After a minimum 1 month of sobriety, patients who fulfilled ICD-10 criteria of alcohol dependence were interviewed for data collection using Alcohol Use Disorders Identification Test (AUDIT), MINI-International Neuropsychiatric Interview (MINI) (Version-6.0) and a specially designed sociodemographic and clinical interview proforma. Subjects with substance use except tobacco were excluded from study. Main group comparison used chi-square test for categorical variables and the t-test for continuous variables. Results: Most of the patients studied were >40 years of age. Majority were employed (92%), lived in nuclear families (78%) and came from rural background (77.5%). Forty five percent of the patients initiated alcohol drinking between 16-25 years and reported peer pressure (50%) as most significant factor responsible for initiation of drinking alcohol. Mean age of developing alcohol dependence was 25.12 years (SD=4.28). Mean AUDIT score for subjects was 27.7 (SD=4.73). Lifetime psychiatric co-morbid disorders were detected in 45%. Psychiatric disorders most frequently associated with alcohol dependence were major depressive disorder (10%), bipolar affective disorder (7.5%), dysthymia (5%), anxiety disorders (7.5%) and antisocial personality disorder (5%). Conclusion: The study indicates that psychiatric disorders are prevalent in alcohol dependents and mood disorders are the most prevalent ones. It was also observed that co-morbid psychiatric disorders are associated with more severe alcohol problems.